Ultrasound-guided foam sclerotherapy for severe chronic venous insufficiency - de-Abreu,Guilherme Camargo Gonçalves (2017)
ABSTRACT Chronic venous insufficiency is characterized by cutaneous alterations caused by venous hypertension; in severe forms, it progresses to lower limb ulcers. Lower limb varicose veins are the main cause of chronic venous insufficiency, and the classic treatment includes surgery and compressive therapy. Minimally invasive alternative treatments for varicose veins include new techniques such as venous thermal ablation using laser or radiofrequency. The use of different methods depends on clinical and anatomical factors. Ultrasound-guided foam sclerotherapy is the venous injection of sclerosing foam controlled by Doppler ultrasound. Sclerotherapy is very useful to treat varicose veins, and probably, is cheaper than other methods. However, until the present, it is the less studied method.